The world around the Old Testament : the people and places of the ancient Near East - Arnold, Bill T.; Strawn, Brent A. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2016)
Leading experts introduce the people and contexts of the Old Testament. What people groups interacted with ancient Israel? Who were the Hurrians and why do they matter? What do we know about the Philistines, the Egyptians, the Amorites, the Assyrians, the Babylonians, and others? In this up-to-date volume, leading experts introduce the peoples and places of the world around the Old Testament, providing students with a fresh exploration of the ancient Near East. The contributors offer comprehensive orientations to the main cultures and people groups that surrounded ancient Israel in the wider ancient Near East, including not only Mesopotamia and the northern Levant but also Egypt, Arabia, and Greece. They also explore the contributions of each people group or culture to our understanding of the Hebrew Scriptures. This supplementary text is organized by geographic region, making it especially suitable for the classroom and useful in a variety of Old Testament courses. Approximately eighty-five illustrative items are included throughout the book. - Publisher.
Introduction / Bill T. Arnold, Brent A. Strawn -- The Amorites / Daniel E. Fleming -- Assyria and the Assyrians / Christopher B. Hays, Peter Machinist -- Babylonia and the Babylonians / David S. Vanderhooft -- Ugarit and the Ugaritians / Mark S. Smith -- Egypt and the Egyptians / Joel M. LeMon -- The Hittites and the Hurrians / Billie Jean Collins -- Aram and the Arameans / K. Lawson Younger Jr. -- Phoenicia and the Phoenicians / Christopher A. Rollston -- Transjordan : The Ammonites, Moabites, and Edomites / Joel S. Burnett -- Philistia and the Philistines / Carl S. Ehrlich -- Persia and the Persians / Pierre Briant -- Arabia and the Arabians / David F. Graf -- Greece and the Greeks / Walter Burkert.
Includes bibliographical references and indexes.
Keywords: Bible. -- History of contemporary events; Middle East -- History -- To 622.; Middle East -- History, Local